1987
DOI: 10.1002/pssa.2210990121
|View full text |Cite
|
Sign up to set email alerts
|

Surface photovoltage spectroscopy of real 〈111〉 GaP surfaces

Abstract: Surface photovoltage spectroscopy measurements are reported for real np, n, and p-type GaP surfaces. Surface energy states are detected within and greater than the energy gap. Changing the surface condition by etching produces changes in the distributions of the surface states prior to etching, this is attributed to the effect of the adsorbed oxygen a t the surface and to changes of the number of disordered Ga and P atoms by etching.Oberflachenphotospannungsspektroskopieuntersuchungen werden an realen np-, n-u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

1989
1989
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 31 publications
1
4
0
Order By: Relevance
“…In such cases the surface parameters are determined with a very low accuracy. The similar situations are observed for all electrical semiconductor investigation methods [22,23].…”
Section: Resultssupporting
confidence: 80%
“…In such cases the surface parameters are determined with a very low accuracy. The similar situations are observed for all electrical semiconductor investigation methods [22,23].…”
Section: Resultssupporting
confidence: 80%
“…Some authors have interpreted super-bandgap structure in terms of surface states found in the energy range of an allowed band [297,298,303,384]. As demonstrated in Fig.…”
Section: Gap State Spectroscopymentioning
confidence: 99%
“…Another venue in which SPS is frequently used is the evaluation of the effect of various treatments, such as electron [101] or ion [349,352] bombardment, etching [352,354], annealing [383,384], lightsoaking [304,306], etc., on semiconductor surfaces. Brillson [363,364,372,373,375,376] has pioneered the use of SPS in tandem with chemical analytical tools in order to assess the impact of surface chemistry on surface electronic properties.…”
Section: Gap State Spectroscopymentioning
confidence: 99%
See 2 more Smart Citations